Change and Influence in the Community Colleges of British Columbia - Levin, John S. (Canadian Journal of Higher Education, 1994)
During the 1980s, a number of social, economic, and political changes in British Columbia enabled individuals and groups to influence actions which affected the operations and development of the community colleges of British Columbia. This is a study of influence and influencers in the community colleges of British Columbia. Examined are actions affecting the British Columbia community col- lege from 1980 1991. Determinants and outcomes of these actions, as well as those individuals or groups who influenced these actions, are identified.